Analisis aktivitas perlindungan sinar UV ekstrak etanol daun kakao (Theobroma cacao L.) berdasarkan nilai Sun Protection Factor. - Rustam, Julis Tina; Maryam, St.; Suhaenah, Asriani (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
UV rays have a bad impact on the skin, but they can be minimized by using ingredients that are UV protective. Sunscreen can be obtained from natural ingredients, one of which is Cocoa Leaves (Theobroma cacao L.) which contains flavonoid and phenolic compounds. The aim of this research was to determine the UV protection activity of ethanol extract of cocoa leaves (Theobroma cacao L.) originating from the Malino, Jeneponto and Wajo areas based on the Sun Protection Factor value. Measurement of the Sun Protection Factor (SPF) value using the UV-Vis Spectrometry method was measured at wavelengths of 290, 295, 300, 305, 310, 315 and 320 nm. The results showed that the ethanol extract of cocoa leaves (Theobroma cacao L.) had UV protection activity for the Malino area at a concentration of 0.01% of 3.25 (minimum protection), a concentration of 0.03% of 10.34 (maximum protection). , 0.05% concentration of 17.10 (ultra protection). For the Jeneponto area, the 0.01% concentration is 3.88 (minimum protection), the 0.03% concentration is 12.3 (maximum protection), the 0.05% concentration is 20.18 (ultra protection) and the Wajo area has a value at a concentration of 0.01% it is 3.38 (minimum protection), a concentration of 0.03% is 10.77 (maximum protection), a concentration of 0.05% is 17.05 (ultra protection). Ethanol extract of cocoa leaves (Theobroma cacao L.) originating from Jeneponto has the greatest UV protection activity with a value of 20.18 with ultra protection ability.